How to be happy at work : - McKee, Annie (Harvard Business Review Press, 2018)
McKee's research reveals that there are three essential elements that people must have in order to be happy at work: A sense of purpose and the chance to contribute to something bigger than themselves; A vision that is powerful and personal, creating a real sense of hope; and Resonant, friendly relationships The book is organized around these essential elements and shows how leaders can create and sustain them in the face of ongoing stress and pressure, as well as how to create a healthy, positive climate for their teams and other groups within their companies. How to Be Happy at Work will transform and enrich our understanding of what it means to be happy at work, and it will provide clear, practical advice and instruction for how to achieve this.